Personalised medicine in paediatrics: individualising treatment in children with rare neurological diseases - Scarpa, Maurizio (Springer Netherlands, 2011)
The development of personalised medicine is of considerable importance for paediatric patient populations, and represents a move away from the use of treatment dosages based on experience with the same compounds in adults. Currently, however, we know little about developmental pharmacogenomics and, although many biomarkers are available for clinical research use, there have been few applications in the management of paediatric diseases. This paper reviews where we are in the journey towards achieving paediatric personalised medicine and describes a group of diseases requiring such an approach. The personalised medicine approach is particularly relevant for the treatment of rare childhood diseases, and the group of life-threatening neurological disorders known as lysosomal storage diseases represents a potential study population. The genetic bases of these disorders are generally well defined, there is the potential for diagnosis at birth or prenatally, and there are a range of therapeutic options available or under development.